Medial Thigh Flap for Scrotal Defect Reconstruction: A Pedicled Approach - Mohd. Altaf Mir; Jaya Jain (Key Flaps in Plastic Surgery, 2023)
This book chapter presents a case report and discussion on the use of the pedicled medial thigh flap (MTF) for reconstructing a scrotal defect with exposed testicles following debridement of Fournier’s Gangrene. The case presentation describes the preoperative condition of the patient and the surgical procedure performed, which involved debridement and reconstruction using a pedicled MTF. The flap was raised from the medial thigh region and transposed to cover the scrotal defect, while the donor site was closed primarily. The postoperative period remained uneventful, and satisfactory results were observed during follow-up examinations. The discussion section introduces the pedicled MTF technique, highlighting its utility in reconstructive procedures for lower extremity and pelvic soft tissue defects. The surgical techniques involved in the procedure are outlined, including patient evaluation and planning, flap design and marking, flap elevation, flap transposition and inset, and donor site closure. Advantages of the pedicled MTF technique include the availability of adequate tissue volume for reconstructing moderate to large defects, reliable blood supply through the medial circumflex femoral artery and vein, versatility in addressing various types of defects, and minimized donor site morbidity. The limitations of the technique, such as the need for detailed preoperative vascular imaging and potential aesthetic changes at the donor site, are also discussed. The abstract emphasizes the practical application and benefits of the pedicled MTF technique in reconstructive surgery. By understanding the surgical techniques and considering the advantages and limitations of the pedicled MTF, healthcare professionals can effectively address complex soft tissue defects in the lower extremities and pelvic region, ultimately improving patient outcomes.